Influence the psychology of persuasion - Cialdini, Robert B. (Collins Imprint of HarperCollins, 2007)
Influence, the classic book on persuasion, explains the psychology of why people say "yes"-and how to apply these understandings. Dr. Robert Cialdini is the seminal expert in the rapidly expanding field of influence and persuasion. His thirty-five years of rigorous, evidence-based research along with a three-year program of study on what moves people to change behavior has resulted in this highly acclaimed book. You'll learn the six universal principles, how to use them to become a skilled persuader-and how to defend yourself against them. Perfect for people in all walks of life, the principles of Influence will move you toward profound personal change and act as a driving force for your success.